Spherical Radiative Transfer in C++ (SRTC++): A Parallel Monte Carlo Radiative Transfer Model for Titan - Barnes, Jason W.; MacKenzie, Shannon M.; Young, Eliot F.; Trouille, Laura E.; Rodriguez, Sèbastien; Cornet, Thomas; Jackson, Brian K.; Ádámkovics, Máté; Sotin, Christophe; Soderblom, Jason M. (The Astronomical journal, 2018)
We present a new computer program, SRTC++, to solve spatial problems associated with explorations of Saturn's moon Titan. The program implements a three-dimensional structure well-suited to addressing shortcomings arising from plane-parallel radiative transfer approaches. SRTC++'s design uses parallel processing in an object-oriented, compiled computer language (C++) leading to a flexible and fast architecture. We validate SRTC++ using analytical results, semianalytical radiative transfer expressions, and an existing Titan plane-parallel model. SRTC++ complements existing approaches, addressing spatial problems like near-limb and near-terminator geometries, non-Lambertian surface phase functions (including specular reflections), and surface albedo nonuniformity.